Upaya Guru Dalam Mengembangkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar Pada Pembelajaran IPS: Studi Literatur - Komalasari, Imas; Ridwan, Ita Rustiati; Alfarisa, Fitri (Didaktika, 2021)
Critical thinking skills for elementary school students are very important to face challenges in the era of globalization. This study aimed to determine: 1) critical thinking skills of elementary school students in social studies learning, 2) supporting and inhibiting factors that influence teachers in developing critical thinking of elementary school students in social studies learning, 3) what efforts can be made by teachers in developing students' critical thinking skills in social studies learning. This study used a qualitative approach with research techniques using literature studies. The occurrence of the Corona Virus 2019 (Covid-19) outbreak and the enactment of social and physical distancing became obstacles for researchers because they could not research directly into the field. The data used were secondary data obtained from books, articles, journals, previous research, as well as data that researchers obtain from the internet in accordance with the research problem being studied by the researcher. The results showed that: 1) students' critical thinking skills in social studies learning are still lacking, 2) 2013 curriculum is a supporting factor for teachers in developing critical thinking, and the inhibiting factor is the use of the lecture method which is continuously used without innovation, 3) efforts that can be made teachers to improve critical thinking in the classroom can use several methods, namely: cooperative learning methods are proven to improve students' critical thinking skills, including the TPS method (Think-Pair-Share), scientific approach, social inquiry, problem-based and or project-based learning, collaborative or cooperative and active-participatory methods, increasing interaction between students, asking open-ended questions or innovative questions that can trigger students' thinking skills.